SINCROBOX® as a method to improve shoulder's function in mastectomized women. Issue 6 (27th June 2018) - Espejo-Reina, A; Becerra, E; Candel, R; Cerezo, MV; Martin, R; Meza, H; Santiago, C; Navarro, A
Objectives: To asses the effect of a sports discipline called SINCROBOX® (consisting in stationary biking coordinated with different arm exercises, namely grip strength, light weightlifts, elastic band stretching, etc) in the functional capacity of mastectomized women's shoulder. Methods: A randomized blinded cohort study was carried out, with 2 groups of mastectomized women (due to breast cancer). The first one (28 patients) was subjected to SINCROBOX® training for three months, while the second one (22 patients) served as control group. Every patient was subjected to physical exam (range of motion measurement of the affected shoulder) and to functional shoulder tests (DASH, Constant, STT and Oxford) before beginning the training and after 3 months of exercise. A Student's T test was performed for statistical analysis in each group. Results: Every variable assessed showed statistically significant advantages in the training group: range of motion increased more than 10° in all directions; SST (+20.9; p<0.001), DASH (-19.8; p<0.001), Constant (+15; p=0.004) and Oxford (+8.6; p< 0.001). There were no differences in the control group, before and after training. No complications were found in both groups. Conclusion: SINCROBOX® is a safe sports discipline that has the ability to improve mastectomized women's shoulder's functional capacity.